A questão das drogas no contexto dos jovens e adolescentes em situação de privação de liberdade em Lagoa Seca/PB - Almeida, Thaís Farias de (2023)
In the context of the current Latin American debate, it has been pointed out that the contemporary phenomena and their challenges require the development of approaches by Popular Education which were not part of its former framework, that is to say, its classical version developed in the 1960s. The issue of drugs, for example, is one of these phenomena. Prohibitionist policies, driven by the warlike vision of the 'war on drugs', have caused an increase in violence, mass incarceration, the extermination of people belonging to the popular classes, the destruction of projects for the future of young people and adolescents, etc. Bearing this in mind, the socio-educational work regarding drugs, under the perspective of Popular Education, constitutes a different alternative to the hegemonic approaches, which are guided by the irrationality of the repressive determinations originating from the warlike vision on such a subject. This research is situated in this thematic field, and its general objective is to analyse how the issue of drugs has been addressed in the school context of young people and adolescents in compliance with the socio-educational measure of internment in the Centro Socioeducativo Lar do Garoto, located in the municipality of Lagoa Seca/PB. In order to achieve its purpose, the research starts from the following specific objectives: 1) to present aspects of the analytical basis of Popular Education that dialogue with the theme of drugs; 2) to focus on the origin of the socio-educational system in Brazil and, more specifically, of the Lar do Garoto; 3) to investigate how teachers have approached drugs in the school context of the Lar do Garoto. From the point of view of its theoretical-conceptual framework, the study takes into account, fundamentally, the contributions of three analytical spheres: Popular Education, Sociology of Deviance and Critical Criminology. Methodologically, this is a qualitative research carried out through unsystematic observations at Lar do Garoto and through semi-structured interviews with teachers from the school of that institution. As a result of the Thematic Analysis conducted, the work reached five categories, which guided the discussion of the results, namely: 1) social profile of young people and adolescents from Lar do Garoto; 2) presence of families at Lar do Garoto; 3) activities developed at Lar do Garoto; 4) relationship of adolescents from Lar do Garoto with drugs; 5) approaches of drugs developed at Lar do Garoto. Among the findings, the following were identified: 1) different approaches to drugs, with approaches guided both by prohibitionist logic and approaches that reject it; 2) lack of specific training for teachers to deal with the issue of drugs; 3) the existence of cases in which teachers develop activities that have similarities with the perspectives of Popular Education, although they do not have systematized knowledge about it. Conclusively, it is emphasised, for example, the essential need to provide continuing training for socio-education teachers, taking into account the challenges involved in approaches about drugs.